A PHILOSOPHY OF EDUCATION: OUR EDUCATIONAL INSTITUTIONS AND THE ECONOMY. Issue 45 (5th January 2017) - Brockless, Adrian
Abstract : The topics of education and the role of educational institutions in society are seldom far from the headlines, the lips of politicians, schoolteachers and parents. Discussion of education (and its associated institutions) within these forums tends to assume uncritically that its ultimate point is to benefit the economy and, by extension, empower the individual through increased prestige and material wealth. This article argues that such a conception of education is misguided and, indeed dangerous, as it estranges us from forms of thought that are frequently united with our conception of what it means to be human, alongside damaging prospects of long-term economic welfare. It is, therefore, the responsibility of our educational institutions to maintain a critical resistance to the culture of the times by ensuring that they do not merely become factories that train their students in ways purely designed to maximize economic impact and increased personal wealth.